A case of celiac disease with type I enteropathy-associated T-cell lymphoma in a Japanese male patient. Issue 3 (3rd July 2019) - Hiraga, Hiroto; Sakuraba, Hirotake; Tanaka, Nahoko; Watanabe, Rina; Akemoto, Yui; Ota, Shinji; Kikuchi, Hidezumi; Sawaya, Manabu; Hiraga, Noriko; Chinda, Daisuke; Hanabata, Norihiro; Mikami, Tatsuya; et al.
Abstract: A 45-year-old Japanese male patient who was diagnosed with celiac disease (CeD) developed type I enteropathy-associated T-cell lymphoma (EATL). In 2013, the patient was admitted to our hospital with worsening of diarrhea and weight loss. Pathological examination of biopsy specimens from the duodenum and ileum led to a diagnosis of suspected EATL. A previous total colonoscopy (TCS) indicated villous atrophy in the terminal ileum. The patient was changed to a gluten-free diet, and the nutritional status gradually improved. In September 2014, he experienced acute right lower abdominal pain. He underwent urgent surgery, and a perforation was identified in the ileum. A diagnosis of type I EATL was made following histopathological examination. After eight courses of CHOP therapy, the patient entered complete remission. TCS and esophagogastroduodenoscopy with magnifying narrow-band imaging performed in 2015 identified villous regrowth in the distal ileum and duodenum. Capsule endoscopy also found villous regrowth in the entire small intestine. To our knowledge, this is the first case of type I EATL following CeD with villous atrophy before EATL occurrence in a Japanese HLA-DQ2 carrier. The possibility of type I EATL occurring after CeD should be recognized, although CeD is quite rare in Japan.